Prevalence of Hepatitis C Virus Infection in Cancer Patients: A Cross-sectional Study from Regional Cancer Care Centre, Gujarat, India - Hirenkumar Ashokbhai Patel; Foram Maulin Patel (Journal of Clinical and Diagnostic Research)
Introduction: Hepatitis C infection is a liver disease caused by the Hepatitis C Virus (HCV). It is one of the major risk factors for acute to chronic liver diseases, such as altered liver functions, chronic hepatitis, cirrhosis, hepatocellular carcinoma and liver failure. Additionally, the HCV poses significant risks to cancer patients undergoing treatment. Understanding the prevalence of HCV infection in cancer patients is crucial. Aim: To determine the prevalence of HCV infection in patients attending a cancer care hospital which may help in the early detection of HCV infection and prevent complications. Materials and Methods: This cross-sectional study was carried out with patients attending the Gujarat Cancer and Research Institute (GCRI), a tertiary care cancer hospital in Gujarat, India, between August 2018 and December 2019 in the Department of Microbiology. A total of 45,886 serum samples were collected and screened for HCV using the Enzyme-Linked Immunosorbent Assay (ELISA). All demographic and clinical information was documented for analysis. Statistical Package for the Social Sciences (SPSS) software was used for data analysis. Results: The study revealed a prevalence of HCV infection of 190 (0.41%) among the cohort. Adult patients residing in rural areas exhibited higher rates of HCV positivity. Solid tumours, particularly those of the digestive system, accounted for 112 (58.9%) of the HCV-positive cases. The surgical oncology units reported the highest proportion of HCV-positive patients, with 115 (60.5%) cases. Risk factors such as blood transfusion and radiotherapy were associated with HCV transmission. Notably, 101 (53.2%) of the positive patients had no identifiable risk factors. Conclusion: Routine screening for blood-borne viruses in cancer patients, especially before immunosuppressive treatments, is crucial. Comprehensive prevention strategies, including the promotion of injection safety, blood safety through screening, and infection control measures, are essential in healthcare settings. These findings underscore the significance of national guidelines and surveillance activities to combat HCV infection effectively.